Clinicobacteriological study of pyoderma with trends in antibiotic sensitivity at a tertiary care center in western India - Kasturi Chavan; Bhavana Ravindra Doshi; Vaishali Dohe (Wolters Kluwer Medknow Publications, 2021)
Background: Pyoderma refers to any pus-forming infection of the skin. Antibiotic resistance has significantly downplayed the utility of established antibiotics and possesses a serious threat to public health. Objective: To study the causative organisms, their trends of antibiotic sensitivity pattern thus helping in prescribing appropriate antibiotics and study the response to the treatment in patients of pyoderma. Materials and Methods: A 2-month prospective study on a cohort of 30 pyoderma patients attending the outpatient and inpatient department in our tertiary care hospital under ICMR short-term studentship was undertaken. Statistical analysis was performed using the SPSS software version 24. Results: Those in 5th-6th decade were more predisposed. Higher incidence was seen in anemics. Staphylococcus spp. (26/30 case 86.66%) was the most common organisms to be isolated in 12/15 (80%) outpatients and 14/15 (93.33%) inpatients. Methicillin-resistant Staphylococcus aureus (MRSA) was isolated equally (33.33%) in both outpatient and inpatients, with increasing trend in MRSA in out-patients. Higher incidence of Pseudomonas aeruginosa in outpatients was noted. MRSA in superficial pyoderma group was sensitive to one first-line drug which was gentamycin, whereas in deep pyoderma, the only first-line drug to which the MRSA was 100% sensitive was ciprofloxacin. All MRSA, MSSA, MR CONS, and MS CONS were sensitive to all second-line drugs. Sixty-percent patients who showed no response to empirical primary line of treatment showed good response on changing the antibiotics according to the reports of culture and sensitivity. Conclusion: An increasing trend in MRSA in outpatients was noticed along with higher incidence of Pseudomonas infection. Limitation: Small sample size.